2017
DOI: 10.18632/oncotarget.18599
|View full text |Cite
|
Sign up to set email alerts
|

Advanced alveolar soft part sarcoma responds to apatinib

Abstract: Alveolar soft part sarcoma (ASPS) is a rare, hypervascular soft tissue sarcoma with a low chemotherapy response rate. Here, we report an ASPS case with multiple lung metastases on initial presentation. The primary tumor, a hypervascular soft tissue mass 4.1×3.2×2.0 cm, located in the right thigh, was resected prior to chemotherapy. The patient suffered disease progression after two cycles of gemcitabine-docetaxel treatment. Immunohistochemical examination of the tumor tissue revealed strong positive staining f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…Our collected data of toxicity (Table ) were differently distributed from what had already been described in clinical trials of apatinib . Our population was much younger than the participants in previous trials , which might influence the distribution of the side effects. Hypertension was not as severe in adolescents.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Our collected data of toxicity (Table ) were differently distributed from what had already been described in clinical trials of apatinib . Our population was much younger than the participants in previous trials , which might influence the distribution of the side effects. Hypertension was not as severe in adolescents.…”
Section: Discussionmentioning
confidence: 92%
“…If a patient exhibited stable disease (SD), then the next evaluation would be performed 2 months later to confirm the SD and then repeated every 2 months thereafter. We strictly followed PR or progressive disease as described in RECIST 1.1 and did not set a minor response as performed by Grignani et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…receiving apatinib. 10 Besides, Li et al reported the efficacy of apatinib at an initial dose of 500 mg in 10 stage IV sarcomas patients who received at least one complete cycle of treatment. 9 Among them, 2 patients achieved PR and 6 had SD; and an encouraging median PFS of 8.84 was detected.…”
Section: Discussionmentioning
confidence: 99%
“…Promising efficacy of apatinib was reported in several subtypes of sarcomas. [6][7][8][9][10] We further retrospectively investigated the outcomes of apatinib in 31 patients with advanced metastatic or recurrent sarcoma who pretreated with at least one chemotherapy regimen or refused to receive chemotherapy. in 7 patients (22.6%) and trunk in 3 patients (9.7%).…”
Section: Introductionmentioning
confidence: 99%